FROM THE CRADLE TO THE GRAVE: AN ANALYSIS OF TERRITORIAL CONFLICTS AND DEATH POLICIES - Guedes Mateus, Luizane (Revista Gênero e Interdisciplinaridade, 2024)
The problem with this paper refers to a brief analysis of urban conflicts in the municipality of Vitória ES. Pointed out as confrontations between rival groups in the vulnerable territories of the city, these conflicts have caused new forms of sociability among residents of the municipality, as well as the need to review the entire public policy apparatus of the city. It seeks to analyze Practical discourses based on the fight against these conflicts, which build a new modality of subjection and extermination of young people, mostly blacks.